Our Agricultural Krísis: Sketches of a Missional Response - Anslow, Matthew (Ecclesial Futures, 2020)
In Australia, and indeed across the world, we are experiencing the effects of a broken food system, such that we face the possibility of a serious agricultural crisis. Current hopes for a resolution to this impending crisis are generally pinned to technology, despite the various problems associated with the use of agricultural technologies over recent decades. Such a situation demands a Christian missional response—an agriculturally-conscious missiology. This paper argues that farming and food production constitutes an aspect of Christian mission. The NT notion of krísis (judgment) is an as opportunity for repentance, applied to suggest that our agricultural crisis is a missional opportunity for the Church since it has spiritual, practical, and traditional resources necessary for a new agricultural paradigm. In light of these resources, the paper makes some provisional suggestions, directed at “consumers,” related to three missiological categories: relationship, contextualization, and participation. Each contributes to a way of thinking that Ellen Davis has called “agrarianism.”